2021
DOI: 10.1038/s41598-021-82689-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk assessment for the development of cardiovascular diseases in the Hungarian general and Roma population

Abstract: Cardiovascular diseases (CVDs) are the number one cause of death globally, and the early identification of high risk is crucial to prevent the disease and to reduce healthcare costs. Short life expectancy and increased mortality among the Roma are generally accepted (although not indeed proven by mortality analyses) which can be partially explained by the high prevalence of cardiovascular risk factors (CVRF) among them. This study aims to elaborate on the prevalence of the most important CVD risk factors, asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…For all CVD risk estimation scores, the average of the estimated risk was higher among Roma compared to the HG independently of sex. The proportion of high-risk group in the Hungarian Roma male population was on average 1.5–3 times higher than in the general one, while among Roma females, the proportion of high-risk groups in the Hungarian Roma female population was on average 2–3 times higher compared to the distribution of females in the general population [ 32 ]. By defining the metabolic syndrome (MetS) prevalence by age groups, we could show that MetS arises earlier among the Roma than in the HG population; while there is no significant difference in MetS prevalence between HG and HR populations in the 20–34 years age group (29.6% and 26.4%, respectively), it is significantly higher in the HR population than in the HG population in the 35–49 years age group (46.7% vs. 31.6%), i.e., in comparison with the prevalence values for the age group of 20–34 years, a significant increase in MetS prevalence can be observed in the age group of 35–49 years among Roma, while in case of the HG population, it can be detected only in the older age group (50–64 years) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…For all CVD risk estimation scores, the average of the estimated risk was higher among Roma compared to the HG independently of sex. The proportion of high-risk group in the Hungarian Roma male population was on average 1.5–3 times higher than in the general one, while among Roma females, the proportion of high-risk groups in the Hungarian Roma female population was on average 2–3 times higher compared to the distribution of females in the general population [ 32 ]. By defining the metabolic syndrome (MetS) prevalence by age groups, we could show that MetS arises earlier among the Roma than in the HG population; while there is no significant difference in MetS prevalence between HG and HR populations in the 20–34 years age group (29.6% and 26.4%, respectively), it is significantly higher in the HR population than in the HG population in the 35–49 years age group (46.7% vs. 31.6%), i.e., in comparison with the prevalence values for the age group of 20–34 years, a significant increase in MetS prevalence can be observed in the age group of 35–49 years among Roma, while in case of the HG population, it can be detected only in the older age group (50–64 years) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased mortality and shorter life expectancy among the Roma are not proven in Hungary (ethnicity is not recorded in the mortality statistics) but can be suspected based on the high prevalence of health risk factors among them. Among the Roma, the frequency of cardiovascular risk factors is higher compared with that among the general population [ 12 , 13 ], and, consequently, their estimated cardiovascular risk is significantly higher, too [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cardiovascular risk factors 16 20 and, thus, the overall estimated cardiovascular risk are significantly higher among the Roma than the host country average 21 . Previous studies have shown that reduced HDL-C levels are very common in the Roma population 22 25 and that the estimated 10-year cardiovascular risk is also significantly higher in the case of both sexes among them than in the Hungarian general population 21 .…”
Section: Introductionmentioning
confidence: 99%